Link between body cellular mass and left ventricular hypertrophy in female and male athletes - Mscherini, G.; Petri, V.; Galanti, G. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Cardiac adaptation to intense physical training is determined by many factors. Differences between the sexes in the left ventricle parameters are well established, however, both sport activity and body composition seem to reduce them. In order to better explain some heart modifications, a first approach was to eliminate the FM from the indexing of the left ventricular parameters. Fat free mass also contains the extracellular mass which does not represent a metabolically active compartment. The aim of this study is to verify the differences between the sexes with a new left ventricular indexation with the metabolically active tissue of the body as body cell mass in elite athletes. METHODS: Twenty-five females were matched with 25 elite male soccer players (females=26.2±1.9 yrs, males=26.5±1.8 yrs; P=NS). An accurate body composition analysis (skinfold and bioimpedance) and an echocardiography were performed. RESULTS: Differences between the sexes in body composition were confirmed in fat mass (fat mass index females=3.5±0.5 kg/m2, males=2.4±0.5 kg/m2, P<0.001), while no differences were found in the extra cellular mass index (females=7.3±1.1 kg/m2, males=7.5±0.5 kg/m2; P=NS). There are no differences in systo-diastolic parameters between sexes. Greater relationships were found between left ventricular mass and body cells (r=0.829, r2=0.686, COV=401.5) compared to fat free mass (r=0.819, r2=0.675, COV=344.7). Left ventricular dimensions show higher values in males who also have the following body cell indexation (females=128.2±15.8 g/m2, males=143.4±14.7 g/m2; P<0.001). CONCLUSIONS: Analyzing body composition in three compartments appears a solution that physiologically can explain some aspects of the athlete`s heart. These results could be considered as preliminary data which can be used to create a new indexation.